Tocotrienol-rich fraction modulates cardiac metabolic profile changes in isoprenaline-induced myocardial infarction rats - Khairul Anwar Zarkasi,; Satirah Zainalabidin,; Tan, Jen-Kit; Nur Haleeda Hakimi,; Nur Zuliani Ramli,; Zakiah Jubri, (Penerbit Universiti Kebangsaan Malaysia, 2020)
In myocardial infarction (MI), the occurrence of energy depletion, oxidative stress, and decreased amino acids metabolism alter tissue metabolites. Evidence has shown that tocotrienol-rich fraction (TRF) prevents myocardial injury in MI. However, the protective mechanism at the metabolite level is unknown. Male Sprague-Dawley rats were grouped into control, isoprenaline (ISO)-induced MI (MI), healthy rats receiving 200 mg/kg TRF (200TRF), and MI rats receiving 200 mg/kg TRF (200TRF+MI) groups. TRF was administered via oral gavage daily for 12 weeks followed by intraperitoneal ISO injection (85 mg/kg) for two consecutive days at a 24-hour interval to induce MI. High-performance liquid chromatography was performed to analyze serum α-tocopherol and tocotrienol concentration whereas ultra-high-performance liquid chromatography-mass spectrometry was used for the untargeted metabolomic study. Serum α-tocopherol but not tocotrienol was increased in the 200TRF (p=0.121) and 200TRF+MI (p<0.05) following TRF supplementation. Multivariate analysis by Orthogonal Projections to Latent Structures Discriminant Analysis showed high predictability of the group comparison models for MI vs control and 200TRF+MI vs MI (cross-validation: Q2>0.7, R2Y>0.8, p<0.05). A total of 84 and 37 metabolites [when covariance of p≥|0.05| (magnitude) and p(corr)≥|0.5| (reliability)] were significantly different in the myocardial homogenates of MI vs control and 200TRF+MI vs MI, respectively. MI rats had reduced S-adenosylmethionine and L-cystathionine that might worsen MI by disturbing glutathione metabolism; decreased phosphoribosyl-pyrophosphate and purine salvage process that might impair DNA synthesis, and elevated glucose-6-phosphate suggesting enhanced anaerobic glycolysis possibly for rapid production of energy. Conversely, TRF supplementation reversed the impaired metabolic pathways caused by MI.